Pan Tadeusz i Kresy : studia językoznawcze - Szpiczakowska, Monika (2022)
PAN TADEUSZ AND THE BORDERLANDS: LINGUISTIC STUDIESThe book presents chosen articles of Monika Szpiczakowska, habilitated doctor and professor of the Jagiellonian University in the years 1993–2018. This material had been already published in scientific journals and collective volumes. It consists of two parts: From the past and present of the Polish language in the Northern Borderlands and About the language of Pan Tadeusz. Altogether, it contains fourteen texts.
Keywords: language of Pan Tadeusz; dialect of the Northern Borderlands; general Polish language